2011
DOI: 10.1085/jgp.201110684
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-selective block of barium permeation through single KcsA channels

Abstract: Ba2+, a doubly charged analogue of K+, specifically blocks K+ channels by virtue of electrostatic stabilization in the permeation pathway. Ba2+ block is used here as a tool to determine the equilibrium binding affinity for various monovalent cations at specific sites in the selectivity filter of a noninactivating mutant of KcsA. At high concentrations of external K+, the block-time distribution is double exponential, marking at least two Ba2+ sites in the selectivity filter, in accord with a Ba2+-containing cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
89
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(107 citation statements)
references
References 48 publications
16
89
2
Order By: Relevance
“…specific inhibitor of KcsA, HmK, a natural and promiscuous blocker, and Hui1 mutants were evaluated to identify toxin segments and residues responsible for specificity and affinity and to discern the mechanism of channel inhibition. The 3D structure of Hui1 determined by NMR, the 1:1 stoichiometry of KcsA inhibition via a pore-directed mechanism, and the role of two, canonical "dyad" residues (Lys 21 and Tyr 22 ) in high-affinity binding all met expectations for a SAK1-type toxin. In contrast, the influence of permeant trans ions (those traversing the channel after entering from the opposite side of the membrane) on dissociation of Hui1 from its external binding site indicated that Arg 23 , a residue with a side chain too bulky to fit snugly into the potassium conduction pore (10), was responsible for the voltage dependence of block rather than Lys 21 .…”
mentioning
confidence: 80%
“…specific inhibitor of KcsA, HmK, a natural and promiscuous blocker, and Hui1 mutants were evaluated to identify toxin segments and residues responsible for specificity and affinity and to discern the mechanism of channel inhibition. The 3D structure of Hui1 determined by NMR, the 1:1 stoichiometry of KcsA inhibition via a pore-directed mechanism, and the role of two, canonical "dyad" residues (Lys 21 and Tyr 22 ) in high-affinity binding all met expectations for a SAK1-type toxin. In contrast, the influence of permeant trans ions (those traversing the channel after entering from the opposite side of the membrane) on dissociation of Hui1 from its external binding site indicated that Arg 23 , a residue with a side chain too bulky to fit snugly into the potassium conduction pore (10), was responsible for the voltage dependence of block rather than Lys 21 .…”
mentioning
confidence: 80%
“…Their malfunction may have disastrous consequences for the organism. Recent studies of ion channels have unravelled many secrets of their structure-function relationship, but their ability to conduct larger ions at almost the free diffusion rate, while discriminating strongly against smaller ions of the same valence remains at the centre of a "many-voiced debate" [1], [2], [3] over decades [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…the potassium channel's ability [6], [8], [9] to conduct up to ∼ 10 8 K + ions per second, while discriminating strongly against the smaller Na + ion. A widelyaccepted explanation of this extraordinary phenomenon is based on the idea of a "snug fit" [4], [6] and an iso-energetic pathway [6], [8], [2] for K + , whereas a Na + ion is confronted by a large free energy barrier. The latter is defined through the Eisenman [5] relation…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations